5-Arylidene derivatives of 3-(benzo[d]thiazol-2-ylamino)-2-thioxothiazolidin-4-one as potential antineoplastic agents – in silico evaluation - Mosula , L.M.; Zhmura, I.O.; Mosula , V.S. (Medicni Perspektivi, 2025)
Computer modeling and in silico prediction of molecular properties are rational approaches in early Drug Development, facilitating the targeted synthesis. One of the promising scaffold for the Drug Design is the rhodanine cycle due to the possibility of introducing substituents in positions 3 and 5. The aim of the work is to study the spectrum of biological activity of a series of 5-arylidene derivatives of 3-(benzo[d]thiazol-2-ylamino)-2-thioxothiazolidin-4-one, predict the affinity for therapeutic targets and establish their possible affiliation to certain codes according to the Anatomical Therapeutic Chemical Classification System of drugs, and predict possible toxicity of hit compounds via the online services. The investigated series of compounds consists of 21 derivatives. In silico prediction was carried out with the use of the web resources SuperPred 3.0, ProTox 3.0. A wide spectrum of biological activity of the derivatives of the series with a predominant antitumour effect is demonstrated. The group structural similarity of compounds to antineoplastic and immunomodulating agents was established. A high probability of group-level efficacy is predicted for the antitumor therapy targets: Krüppel-like factor 5, Nuclear factor erythroid 2-related factor 2, and DNA-(apurinic/apyrimidinic site) lyase. Compounds 3 ((ethyl (E)-4-(2-(2-((3-(benzo[d]thiazol-2-ylamino)-4-oxo-2-thioxothiazolidin-5-ylidene)methyl)-4-chlorophenoxy)acetamido)benzoate)), 4 ((E)-2-(2-((3-(benzo[d]thiazol-2-ylamino)-4-oxo-2-thioxothiazolidin-5-ylidene)methyl)-4-chlorophenoxy)-N-(4-sulfamoylphenyl)acetamide) and 9 ((E)-2-(2-((3-(benzo[d]thiazol-2-ylamino)-4-oxo-2-thioxothiazolidin-5-ylidene)methyl)-4,6-dimethylphenoxy)acetamide) can be considered as hit compounds. With high predictive model accuracy, their potential impact on the specified targets is 99.43%, 95.88%, and 96.92%, respectively. Compound 3 is a potential multi-hitter. The obtained results confirmed the viability of further in vitro, in vivo research.